Seasonal Variation in Nutrient Utilization and Growth Performance of Small Ruminants Under Grazing on Silvipasture System - Das, Madan Mohan (Indian Journal of Animal Nutrition, 2021)
Seasonal variation in chemical composition as well as nutrient utilization and growth performance of Jalauni lambs and Bundelkhandi kids were studied under grazing on two tier silvipasture consisting (stocking rate of 2ACU/ha) of Hardiwickia binata tree (one tier) and grass species namely Cenchrus ciliaris, Crysopogon fulvus, Panicum maximum and Stylosanthes hamata(another tier) during growing (August-October) as well as post growing (November-January) seasons in Bundelkhand region along with supplementation(1% of body weight) of concentrate mixture. Average dry matter(DM) content of pasture forages increased with advancement of maturity from 31.56% during growing season to 49.44% in post growing season, with concomitant increase in neutral detergent fiber(NDF) content from 70.23% to 73.11% and reduction in crude protein(CP) content from 8.29% to 5.45%. DM intake was comparable in both the species ,however, significantly(P<0.05) higher in growing than post growing season. Similarly digestibility of nutrients namely DM, OM, NDF and CP were higher in growing season than post growing season in both the species. Intake (g/W 0.75) of digestible crude protein(DCP)in both lambs and kids was higher(5.76 vs 5.64) in September as compared to December(2.98 vs 3.14). Metabolizable energy (ME) intake (kj/W 0.75) also followed the same trend. Daily live weight gain(g/d) in both lambs and kids was comparable, however, significantly(P<0.05) higher in growing season than post growing season. It was concluded that nutrient intake, nutrient utilization and growth performance were significantly (P<0.05)affected during post growing season due to deterioration of nutritive value of available pasture biomass ,however, comparable results were observed in both the species.